Delivery Time Prediction Using Support Vector Machine Combined withLook-back Approach (Aintelia Science Notes, 2022)
Delivery time refers to the time elapsed from the moment the order is created to the delivery of the product tothe final consumer. It is extremely important to predict the delivery time in order to ensure customersatisfaction and smooth logistics processes. The aim of this study is to predict the delivery time using SupportVector Machine (SVM) with and without consecutive look-back and periodic look-back approaches. A sampledataset obtained from Kaggle was used. Mean Absolute Error (MAE) was utilized to evaluate the performanceof the prediction models. According to the results, the average MAE obtained with the look-back approach(3.81) was 59.12% lower than that obtained without the look-back approach (9.32).
Keywords: Delivery time prediction; Look-back approach; Machine learning; Support Vector Machine